Pendayagunaan Dana Sosial Bank Syariah Melalui Platform Financial Technology untuk Pemberdayaan UMKM pada Era Digital - Rizky Andrean; Nor Fatmah Rahmawati; M. Khoirul Fikri; Agus Fakhrina (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to describe the empowerment of MSMEs in the digital era based on the utilization of social funds by Islamic banks through financial technology platforms. This research is qualitative research with a type of literature research. This study uses secondary data sourced from books, scientific journals, mass media news, as well as sources from the internet which are considered credible and of both national and international standards and are relevant to the matter being studied. Apart from that, to support this research, primary data sources were also used which came from the results of interviews which were studied further through focus group discussion (FGD) activities. The results of the study show that Indonesia is a country with a large potential for MSMEs. The main problem faced in empowering MSMEs is limited access to financing because many MSMEs are not yet bankable. On the other hand, Indonesia also has alternative potential for MSME financing through the utilization of Islamic bank social funds consisting of zakat companies and corporate social responsibility (CSR). In the digital era, this financing can be channeled through financial technology platforms. To be more competitive, the benefits of MSME beneficiaries are not only access to financing but also business empowerment outside of financing aspects such as training and so on provided by the MSME Center which is owned/formed by the financial technology platform.